Impacto do enforcement fiscal na relação entre ciclos econômicos e tax avoidance - Teodósio, Igor Rodrigo Menezes (2022)
Adverse economic scenarios on which companies face resource shortage issues and increase in financial, bankruptcy risks; and the government undergoes reduction in revenue collection, provide the opportunity to investigate the role of tax enforcement whether as an instrument of reduction or not of companies’ aggressive tax avoidance practices throughout the economic cycles. Therefore, the present study aims to investigate the moderating impact of tax enforcement on the relationship between economic cycles and companies’ tax avoidance level. The sample is composed of 28.218 companies with shares traded in the capital Market of countries belonging to the Organization for Economic Cooperation and Development (OCDE), in the period from 2000 to 2020, totaling 218.946 observations. The tax avoidance level was measured in accordance with the models proposed by Atwood et al. (2012), and Tang (2014). The economic cycle phases were classified based on Schumpeter’s (1939) model, whereas the level of tax enforcement was measured by the index for tax evasion by the IMD World Competitiveness Online (IMDWCC). For data analysis, descriptive statistical and correlation analyses techniques were used along with multiple regressions with panel data by the Ordinary Least Squares (OLS). The results of the regression model demonstrated that tax avoidance is influenced by the countries’ economic cycle inasmuch as, in the expansion phase, there is a rise on the tax avoidance level practiced by companies, while in the economic contraction and recession phase, companies tend to adopt a smaller number of tax reduction practices. Yet, it was verified that tax enforcement moderates this relationship providing clues that, in periods of economic growth, taxation authorities adopt a more elevated level of tax execution aiming to mitigate companies’ aggressive tax avoidance practices and increase the Government tax proceeds. On the other hand, in periods of either economic recession or economic upturn, the regulators adopt a lower level of tax execution to engage companies in tax avoidance practices with the goal of minimizing the effects caused by the macroeconomic scenario. Hence, this research contributes to the literature on the influence of economic, institutional factors over tax and corporate decisions as well as the results contribution that might assist investors, regulators and managers in their decisionmaking processes considering different economic scenarios.